The long and short of microRNA. - Yates, L; Norbury, C; Gilbert, R (2013)
MicroRNAs (miRNAs) are versatile regulators of gene expression in higher eukaryotes. In order to silence many different mRNAs in a precise manner, miRNA stability and efficacy is controlled by highly developed regulatory pathways and fine-tuning mechanisms both affecting miRNA processing and altering mature miRNA target specificity.